PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN BUDAYA ORGANISASI TERHADAP KOMITMEN ORGANISASI DAN KINERJA KARYAWAN PADA PT. SASJAM RIRI DI KABUPATEN GIANYAR - Winie Kaori Intan M, Ni Kadek; Ketut Sintaasih, Desak; Ganesha Rahyuda, Agoes (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2017)
The impact of employee’s performance is one of the important value thing that needs a specific concern, regarding it’s connection to the company’s long term journey. The main purpose of this research is to analyze the effect of transformational leadership and organization culture towards organizational commitment and employee’s performance. This research is conducted in PT. Sasjam Riri in Gianyar regentcy. The research itself is taking all the member of its employee in the company, which is consist of  83 people. Sampling technique that used in this research is census method, which is also involving all population of all research sample. The research’s instrumentt is using questionnaire and path analysis as based for data analysis technique. The result of the research states that, the tranformasional leadership and organization culture into its commitment would give a good effect simulataneously and also partially to  the improvement of the employee’s performance. The result also approved that the commitment is making a variable relation between transformational leadership or organization culture and its eemployee’s performance, inside the entity. The implication of this research is that the employee’s performance of PT. Sasjam Riri’s getting better if the leader shows a transformational leadership style and the employees follows the oorganization culture, that has been agreed by all the employees, therefore it can give an improvement to the employee’s performance throughout the organization’s commitment strengthening.